Evaluating the Usability of a Virtual Reality Information System for Children - Jamshid, Beheshti; Large, Andrew; Clement, Ian; Tabatabaei, Nahid (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
We report on a pilot project to evaluate the usability of the VRLibrary, a desktop virtual reality library containing links to websites, depicted as books. While lack of instructions may have prevented the participants in the pilot study from completing the experimental tasks efficiently, they endorsed enthusiastically the VRLibrary. Nous présentons un projet préliminaire conçu pour évaluer l’utilisabilité de la VRLibrary, une bibliothèque de réalité virtuelle de bureau offrant des liens vers des sites web illustrés par des livres. Malgré le manque de directives offertes aux participants au moment de l’étude préliminaire afin d’effectuer efficacement les tâches expérimentales, les participants se montrent enthousiastes envers la VRLibrary.